A Study of Stylistic Features of Cricket Commentary: A Discourse Analysis - Hamid Naveed; Hazrat Umar (NUST Journal of Social Sciences and Humanities, 2021)
This study is based on the analysis of language practices and features that different cricket commentators use in international cricket matches. This study explores that cricket commentary forms a complete register on its own with its field, tenor, and mode components. Data for this research have been taken from the 1992 World Cup, the 2015 World Cup, and the Ashes Series 2005 matches available on YouTube. Textual analysis technique has been employed for data analysis. After analyzing the data in the light of Halliday’s notion of register comprising field, tenor, and mode, it is found that cricket commentary is characterized by special syntactic features such as ellipsis, extensive use of exclamatory sentences, the abundant use of the simple present tense and simple sentences, passive construction notably in elliptical form, first and third conditionals, and inversion. Use of idioms, certain action verbs, certain positive and negative adjectives, and certain adverbs are some of the salient features of cricket commentary. Cricket commentary also has a special jargon with words like ‘knock’, ‘mid-on’, ‘mid-off’, ‘innings’ and ‘bouncer’ etc. Cricket commentators also use certain aspects of connected speech such as weak forms of words, elision, and assimilation.